Taxonomic revision of the species group rubripes of Corinna Koch, 1842 (Araneae; Corinnidae) - Rodrigues, Bruno V.b.; Bonaldo, Alexandre B. (Zootaxa, 2014)
The species of the group rubripes, which harbors the type species of the genus Corinna C. L. Koch, 1842, are revised, including 20 Neotropical species. Three previously known species are re-diagnosed: Corinna rubripes C. L. Koch, 1842, Corinna nitens (Keyserling, 1891) and Corinna mourai Bonaldo, 2000. New records of Corinna nitens are provided, including the first ones from Peru and Bolivia. Seventeen new species, all from Brazil, were described: C. aechmea n. sp., C. balacobaco n. sp., C. caatinga n. sp., C. demersa n. sp., C. escalvada n. sp., C. hyalina n. sp., C. jecatatu n. sp., C. kuryi n. sp., C. loiolai n. sp., C. maracas n. sp., C. regii n. sp., C. telecoteco n. sp., C. tranquilla n. sp., C. vesperata n. sp., C. vilanovae n. sp., C. zecarioca n. sp. and C. ziriguidum n. sp. A key for all twenty species of the group is presented.